2010
DOI: 10.1631/jzus.b0900397
|View full text |Cite
|
Sign up to set email alerts
|

Piper sarmentosum as an antioxidant on oxidative stress in human umbilical vein endothelial cells induced by hydrogen peroxide

Abstract: Endothelial cell death due to increased reactive oxygen species (ROS) may contribute to the initial endothelial injury, which promotes atherosclerotic lesion formation. Piper sarmentosum (PS), a natural product, has been shown to have an antioxidant property, which is hypothesized to inhibit production of ROS and prevent cell injury. Thus, the present study was designed to determine the effects of PS on the hydrogen peroxide (H(2)O(2))-induced oxidative cell damage in cultured human umbilical vein endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 36 publications
3
59
2
Order By: Relevance
“…The endothelial cells lining the blood vessels are very sensitive to injury caused by oxidative stress. Damage to endothelial cell structure and function contributes to blood vessel diseases, including atherosclerosis, thrombosis and vasculitis (Hafizah et al, 2010). Additionally, ROS activate transcriptional messengers, such as NF-κB and activator protein-1 (AP-1), both of which upregulate the production of inflammatory cytokines and mediators.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The endothelial cells lining the blood vessels are very sensitive to injury caused by oxidative stress. Damage to endothelial cell structure and function contributes to blood vessel diseases, including atherosclerosis, thrombosis and vasculitis (Hafizah et al, 2010). Additionally, ROS activate transcriptional messengers, such as NF-κB and activator protein-1 (AP-1), both of which upregulate the production of inflammatory cytokines and mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, human umbilical vein endothelial cells (HUVEC) are commonly used to study vascular dysfunction (Hafizah et al, 2010). Further, hydrogen peroxide (H2O2) is a principal mediator of ROS-dependent signaling, and exposure of endothelial cells to H2O2 induces the activation of ROS-dependent signaling cascades (Eligini et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous and ethanol extracts of root, stem, leave and fruit have been investigated for antioxidant activity using two in vitro models, β-carotene linoleate model and DPPH model, and these studies have shown that ethanol extracts of leaves and fruit are having good antioxidant activity (Hussain et al, 2009a). Aqueous extracts (10% w/v) of the plant have also exhibited ferric reducing antioxidant power due to their high phenolic contents (Hafizah et al, 2010).…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…Ex vivo models: Aqueous, methanol and hexane extracts of leaves in a concentration range 100, 150, 250 and 300 μg/mL have shown preservation of the levels of malondehyde, superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidise (GPx) in human umbilical vascular endothelial cells (HUVECs) (cell line), during H 2 O 2 -induced oxidative stress (Hafizah et al, 2010). Ten percent aqueous extract of the plant in a dose of 150 µg/mL has shown marked induction of NO in HUVECs (Ugusman et al, 2010).…”
Section: Antioxidant Activitiesmentioning
confidence: 99%